Nível de ansiedade, depressão e problemas relacionados ao uso de álcool em funcionários de uma universidade pública. - Silva, Mariana Barbosa da [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The social and economic changes, the adoption of new technologies and the precariousness of labor relations, which are currently occurring, have reflected intensely on the workers’ health. In the globalized era, the worker participates in a scene of high competitiveness and fierce competition. Specially the health professional performs activities that has a high degree of responsibility, needs agility of decision and lives daily with strenuous physical and psychological loads; putting your own physical and mental health at risk. Based on this context, the objective of the study was to estimate the prevalence of anxiety and depression and to identify problems related to alcohol abuse and furthermore to verifying the existence of an association between these factors and sociodemographic and labor variables of teachers and technical-administrative employees of Faculdade de Odontologia (FO) and Medicina Veterinária (FMV) de Araçatuba - Universidade Estadual Paulista. For these to happen, the database was analyzed from January 2013 to October 2019, referring to the questionnaires applied annually during the periodic examination of employees and teachers of the institutions. They consist of the Hospital Anxiety and Depression Scale (Hospital Anxiety and Depression Scale - HADS), for the assessment of anxiety and depression; in the Alcohol Use Disorder Identification Test (AUDIT) for the identification of dangerous use and dependence on alcohol and in the Self-Report Questionnaire (SRQ) for tracking disorders non-psychotic, called Common Mental Disorders (CMD), which include complaints of anxiety, depression, sleep disorders, weariness and somatization and psychotic disorders. The Epi Info 7.2 program was use for data tabulation and BioEstat 5.0 for data analysis. In the period of analisis, 2971 periodic examinations were performed, with 569 (19.2%) showing some alteration. Of these, 429 (75.4%) had changes in the HADS anxiety questionnaire, 254 (44.6%) in HADS depression, 81 (14.2%) in AUDIT and 312 (54.8%) in SRQ. The mean age was 52.23 years (sd = 8.62). The majority were female 326 (57.3%), 366 (64.3%) technical-administrative employees and 383 (67.3%) of the FO. It was find an relation between CMD and problems related to 8 alcohol use with sociodemographic variables: HADS anxiety x sex, HADS anxiety x function, HADS depression x sex, AUDIT x sex, AUDIT x function, SRQ x sex, SRQ x unit. Also among the instruments used: HAD anxiety x AUDIT, HAD depression x AUDIT, SRQ x HAD depression and SRQ x AUDIT. It is settle that the prevalence of CMD and problems related to alcohol use in the population is low. There is an association between these factors and sociodemographic and labor variables.

As mudanças sociais e econômicas, a adoção de novas tecnologias e a precarização das relações de trabalho, que ocorrem atualmente, têm refletido intensamente na saúde dos trabalhadores. Na era globalizada, o trabalhador participa de um cenário de alta competitividade e concorrência acirrada. Os profissionais da área da saúde, em especial, desempenham atividades que apresentam alto grau de responsabilidade, necessitam agilidade de decisão e convivem diariamente com cargas físicas e psíquicas extenuantes; o que coloca em risco sua saúde física e mental. Baseado nesse contexto, o objetivo do trabalho foi estimar a prevalência de ansiedade e depressão e identificar problemas relacionados ao uso de álcool; além de verificar a existência de associação entre esses fatores e variáveis sociodemográficas e laborais de docentes e funcionários técnico-administrativos das Faculdades de Odontologia (FO) e Medicina Veterinária (FMV) de Araçatuba– Universidade Estadual Paulista. Para isso, foi analisado o banco de dados no período de janeiro de 2013 a outubro de 2019, referente aos questionários aplicados anualmente durante o exame periódico dos funcionários e docentes das instituições. Constituem-se na Escala Hospitalar de Ansiedade e Depressão (Hospital Anxiety and Depression Scale - HADS), para a avaliação da ansiedade e depressão; no Teste de Identificação de problemas relacionados ao uso de álcool (Alcohol Use Disorder Identification Test – AUDIT), para a identificação do uso nocivo e dependência de álcool e no Questionário de auto relato (Self-Report Questionnaire – SRQ), para rastreamento de transtornos não-psicóticos, denominados Transtornos Mentais Comuns (TMC), que incluem queixas de ansiedade, depressão, alterações de sono, fadiga e somatizações e os transtornos psicóticos. Utilizou-se o programa Epi Info 7.2 para tabulação dos dados e BioEstat 5.0 para análise dos dados. No período analisado, foram realizados 2971 exames periódicos, sendo que 569 (19,2%) apresentaram alguma alteração. Desses, 429 (75,4%) apresentavam alteração no questionário HADS ansiedade, 254 (44,6%) no HADS depressão, 81 (14,2%) no AUDIT e 312 (54,8%) no SRQ. A média de idade foi de 52,23 anos (dp=8,62). A maioria era do sexo feminino 326 (57,3%), 366 6 (64,3%) servidores técnico-administrativos e 383 (67,3%) da FO. Observou-se associação entre TMC e problemas relacionados ao uso de álcool com variáveis sociodemográficas: HADS ansiedade x sexo, HADS ansiedade x função, HADS depressão x sexo, AUDIT x sexo, AUDIT x função, SRQ x sexo, SRQ x unidade. Também entre os instrumentos utilizados: HAD ansiedade x AUDIT, HAD depressão x AUDIT, SRQ x HAD depressão e SRQ x AUDIT. Conclui-se que a prevalência de TMC e problemas relacionados ao uso de álcool na população é baixa. Existe associação entre esses fatores e variáveis sociodemográficas e laborais.
Level of anxiety and depression and problems related to alcohol use in employees of a public university.
Keywords: Depression; Depressão; Ansiedade; Saúde do Trabalhador; Educação superior